2019
DOI: 10.1088/1752-7163/aafc6f
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis: prevalence and association with oral etiological factors in children and adolescents

Abstract: Halitosis is a condition that can have negative social impacts. Although common, its prevalence and associated etiological factors have been studied little in the child/adolescent population. The aim of the present study was to associate the occurrence of halitosis with oral etiological factors in children aged 6–12 years. A cross-sectional study was conducted with 150 male and female children and adolescents. The organoleptic test (OT) was used to determine halitosis. All patients and caregivers answered a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 24 publications
0
36
0
3
Order By: Relevance
“…Halitosis has a worldwide occurrence, and its prevalence has been evaluated in different population groups, varying from around 5% to 65% (Cortelli, Barbosa, & Westphal, ; Du, Li, Jiang, Zheng, & Zhang, ; Guedes et al, ; Rösing & Loesche, ). Overall, the occurrence of this condition was determined to be significant and high (Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Halitosis has a worldwide occurrence, and its prevalence has been evaluated in different population groups, varying from around 5% to 65% (Cortelli, Barbosa, & Westphal, ; Du, Li, Jiang, Zheng, & Zhang, ; Guedes et al, ; Rösing & Loesche, ). Overall, the occurrence of this condition was determined to be significant and high (Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…An unpleasant odor may occur because of food residue between the teeth and putrefaction of the retained exfoliated oral epithelial cells, and this may increase the plaque accumulation on the teeth and tongue, resulting in more severe bad breath [ 10 , 11 ]. In a study of children and adolescents aged 12–16 years by Guedes et al (2019), subjects with dental caries had a 3.8-fold higher risk of bad breath than those without, and decreased salivary flow increased the risk of bad breath 4.2-fold times [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The KYRBS (2017) reported that over 20% of adolescents answered that they had an unpleasant smell in their mouth, suggesting that the prevalence of bad breath in Korean adolescents is extremely high [ 19 ]. Bad breath can have a negative psychological and social effect on adolescents and can be a sign of other diseases [ 11 , 12 ]. Therefore, it is crucial to identify the cause of bad breath in adolescents and make appropriate interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are primarily involved in halitosis produced by Gram-negative anaerobic oral bacteria (260). Frequently, halitosis can occur due to compromised oral health and oral hygiene, oral infections, xerostomia, tongue coating, dental caries, and periodontitis (261,262). The other individuals who experience halitosis include those with ear, nose, and throat infections (263) and higher levels of urea nitrogen in their blood, especially when it reaches >55 mg/dL (264).…”
Section: Halitosismentioning
confidence: 99%